2019
DOI: 10.1242/dmm.037697
|View full text |Cite
|
Sign up to set email alerts
|

BCL-3 promotes a cancer stem cell phenotype by enhancing β-catenin signalling in colorectal tumour cells

Abstract: To decrease bowel cancer incidence and improve survival, we need to understand the mechanisms that drive tumorigenesis. Recently, B-cell lymphoma 3 (BCL-3; a key regulator of NF-κB signalling) has been recognised as an important oncogenic player in solid tumours. Although reported to be overexpressed in a subset of colorectal cancers (CRCs), the role of BCL-3 expression in colorectal tumorigenesis remains poorly understood. Despite evidence in the literature that BCL-3 may interact with β-catenin, it is perhap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 82 publications
4
35
0
Order By: Relevance
“…We further explain the mechanism of miR-10b to cell proliferation in CRC. Cyclin D1 is one of the most important regulators of the cell cycle, because its degradation leads to G1 cell cycle arrest and inhibits cell growth [18,19]. Our data showed that the inhibition of miR-10b was sufficient to cause the down-regulation of cyclin D1 expression, and this reflects the potential of miR-10b in promoting cell cycle through KLF4 mediated signalling pathway as described in Figure 5.…”
Section: Discussionsupporting
confidence: 51%
“…We further explain the mechanism of miR-10b to cell proliferation in CRC. Cyclin D1 is one of the most important regulators of the cell cycle, because its degradation leads to G1 cell cycle arrest and inhibits cell growth [18,19]. Our data showed that the inhibition of miR-10b was sufficient to cause the down-regulation of cyclin D1 expression, and this reflects the potential of miR-10b in promoting cell cycle through KLF4 mediated signalling pathway as described in Figure 5.…”
Section: Discussionsupporting
confidence: 51%
“…Both studies report that at least 30% of colorectal tumours had increased nuclear expression of BCL-3 (24,25). More recently high BCL-3 expression has been associated with worse survival in CRC (22) Importantly, there are a number of studies that begin to shed light on the mechanism(s) by which BCL-3 can promote colorectal carcinogenesis; we have shown that BCL-3 expression promotes AKT mediated cell survival and drives colorectal tumour growth in vivo (21), BCL-3 has also been reported to increase the stability of c-MYC via ERK activation (23). In addition, (14) BCL-3 has been implicated in promoting tumorigenesis through inhibition of DNA damage induced p53 activation by up-regulating MDM2 expression (44), and to induce cyclin D and cell cycle progression (45).…”
Section: Discussionmentioning
confidence: 99%
“…BCL-3 has been found to be widely expressed in solid tumours (18); in particular, elevated levels of BCL-3 and p52 homodimers have been linked to immortalized human breast epithelial cells (19) and BCL-3 has been proposed as a link between STAT3 signalling and NF-κB in (4) metastatic breast cancer (20). Furthermore, it has been shown that BCL-3 can promote colorectal tumorigenesis by increasing colorectal cancer cell survival through AKT activation (21), through stabilizing c-MYC protein via ERK activation and by promoting the cancer stem cell phenotype by enhancing β-catenin signalling (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL-3 selectively regulated the transcription of intestinal stem cell genes and Wnt targeting leucine rich repeat containing G protein-coupled receptor 5 (LRG5) and achaete-scute family bHLH transcription factor 2 (ASCL2), thereby promoting the cancer stem cells phenotype. Furthermore, they proposed that BCL-3 played a driving role in stem cell phenotype in CRC, which might promote the plasticity and therapeutic resistance of tumor cells [51].…”
Section: Discussionmentioning
confidence: 99%